2021
DOI: 10.3389/fnhum.2021.655116
|View full text |Cite
|
Sign up to set email alerts
|

Functional Cortical Connectivity Related to Postural Control in Patients Six Weeks After Anterior Cruciate Ligament Reconstruction

Abstract: Whereas initial findings have already identified cortical patterns accompanying proprioceptive deficiencies in patients after anterior cruciate ligament reconstruction (ACLR), little is known about compensatory sensorimotor mechanisms for re-establishing postural control. Therefore, the aim of the present study was to explore leg dependent patterns of cortical contributions to postural control in patients 6 weeks following ACLR. A total of 12 patients after ACLR (25.1 ± 3.2 years, 178.1 ± 9.7 cm, 77.5 ± 14.4 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…In this context, athletes after ACLR, may require higher involvement of neurocognitive resources in the frontal cortex for precise joint positioning or lower limb force control [ 9 , 10 ]. Moreover, high activations involving parieto-occipital cortical areas associated with spatial cognition and orientation, as well as visual-motor processing, have been found linked to motor control during functional motor tasks [ 32 , 68 ]. Unfortunately, sensorimotor control of the injured lower extremity may appear to rely on visual information processing and cortical motor planning [ 89 ].…”
Section: Consider Neurophysiological Effects Of Acl Injury Ii: Neurop...mentioning
confidence: 99%
“…In this context, athletes after ACLR, may require higher involvement of neurocognitive resources in the frontal cortex for precise joint positioning or lower limb force control [ 9 , 10 ]. Moreover, high activations involving parieto-occipital cortical areas associated with spatial cognition and orientation, as well as visual-motor processing, have been found linked to motor control during functional motor tasks [ 32 , 68 ]. Unfortunately, sensorimotor control of the injured lower extremity may appear to rely on visual information processing and cortical motor planning [ 89 ].…”
Section: Consider Neurophysiological Effects Of Acl Injury Ii: Neurop...mentioning
confidence: 99%
“…To account for this possibility in our sample, we selected the EEG channel that maximized peak beta and gamma coherence from three channels approximating the motor cortex. Similar region of interest approaches have been used in connectivity analyses (54) and would address the concern of cortical reorganization. In the future, source space reconstruction and connectivity analyses of all pertinent cortical areas may further address this limitation while providing insight into the role of multisensory integration impairments in descending cortical drive.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies utilizing methods to assess central processing in the visual centers demonstrated greater activity in these centers as compared to healthy controls during simple motor tasks. 21,35,98,100,113 It has previously been suggested that increased reliance on the visual system may increase the risk of sustaining a primary ACL injury, potentially as a result of the athlete either missing environmental cues or reacting slowly to a stimulus, thereby executing a movement with poorer technique. 121 Therefore, increased reliance on the visual system identified in individuals following ACLR may have an implication for increased risk of second ACL injury.…”
Section: Changes That Occur In the Somatosensory And Visual Systems F...mentioning
confidence: 99%
“…Along with identifying methods to reduce visual reliance, knowing when to implement these methods is important as well. Proprioception deficits have been identified within the first four weeks following ACLR, 91 and Lehmann et al 113 have also demonstrated that increased reliance on the visual system (at the central processing level) may begin within six weeks following ACLR. The results suggest that clinicians aiming to reduce reliance on the visual system need to implement interventions very soon post-operatively.…”
Section: Clinical Implications For Rehabilitationmentioning
confidence: 99%